Guinbot-an Irrigators Service Association, Inc It's contribution to democratization and development. - Oriondo, Ben G. (Ben G. Oriondo, 2009)
In recent years, people have been interested in discussions about the changes of agricultural production in the world caused by global warming. From another viewpoint, I noticed that with current conditions, agricultural productions changes a great deal every year depending on various factors.